Corticosteroid-binding globulin is a biomarker of inflammation onset and severity in female rats. Issue 2 (August 2016) - Hill, Lesley A; Bodnar, Tamara S; Weinberg, Joanne; Hammond, Geoffrey L
Abstract : Plasma corticosteroid-binding globulin (CBG) plays a critical role in regulating glucocorticoid bioavailability and is an acute phase 'negative' protein during inflammation. In an adjuvant-induced arthritis model, plasma CBG levels decrease in rats that develop severe inflammation, and we have now determined when and how these reductions in CBG occur. After administering complete Freund's adjuvant or saline intra-dermally at the tail base, blood samples were taken periodically for 16days. In adjuvant-treated rats, decreases in plasma CBG levels matched the severity of inflammation, and decreases were observed 4days before any clinical signs of inflammation. Decreases in CBG levels coincided with an ~5kDa reduction in its apparent size, consistent with proteolytic cleavage, and cleaved CBG lacked steroid-binding activity. At the termination of the experimental period, hepatic Cbg mRNA levels were decreased in rats with severe inflammation. While plasma TNF-α increased in all adjuvant-treated rats, increases in Il-4, IL-6, IL-10, IL-13 and IFN-γ were only observed in rats with cleaved CBG. Rats with cleaved CBG also exhibited increased spleen weights, and strong negative correlations were observed among CBG, IL-6 and spleen weights, respectively. However, there were no differences in hepatic Cbg mRNA levels in relation to the apparent proteolysis of CBG, suggesting that CBG cleavage occurs before changes in hepatic Cbg expression. Our results indicate that the levels and integrity of plasma CBG are biomarkers of the onset and severity of inflammation. Dynamic changes in the levels and function of CBG likely modulate the tissue availability of corticosterone during inflammation.